Effects of pH on the structure and mechanical properties of dried pH-responsive latex particles. Issue 41 (3rd October 2017) - Sekido, T.; Kappl, M.; Butt, H.-J.; Yusa, S.; Nakamura, Y.; Fujii, S.
Abstract : Effects of pH on the structure and rigidity of dried bulk pH-responsive latex particles were investigated. Abstract : Micrometer-sized monodisperse polystyrene (PS) particles carrying a pH-responsive poly[2-(diethylamino)ethyl methacrylate] (PDEA) colloidal stabilizer were synthesized via free radical dispersion polymerization. X-ray photoelectron spectroscopy and electrophoretic measurements verified that PDEA covered the PS particle surface. At pH 3.0 and 6.3, where the PDEA is protonated and cationically charged, the PDEA-PS particles were well dispersed in aqueous media thanks to the water soluble PDEA stabilizer and slowly sedimented due to gravity and enriched at the bottom of the glass vials. At pH 10.0, where the PDEA is non-protonated and neutral, the PDEA-PS particles weakly aggregated due to non-hydrated and collapsed PDEA. These PDEA-PS particles and aggregates sedimented to the bottom. The sediment height observed at pH 10.0 was higher than those observed at pH 3.0 and 6.3 in both wet and dry systems, which indicated that a larger porosity was formed at pH 10.0. Mechanical testing experiments confirmed that the fracture toughness of the dried materials decreased with an increase of pH. The fracture toughness was found to be correlated with the degree of particle ordering in the dried particulate materials: more ordered, dense packings lead to a higher fracture toughness compared to amorphous, less dense packings. Thus, we could tune fracture toughness and degree of particle ordering by controlling the pH.